Cultural reality of nyogug pendhalungan: social unearned revenues (ethnososiology pendhalungan approach) - Whedy Prasetyo; Akhmad Toha (Universitas Hayam Wuruk Perbanas, 2023)
This qualitative research on pendhalungan etnososiology aims to reveal nyogug cultures. Cultural tradition helps the wedding feast as a sacrificial unit of present and future economic resources that are certainly to be returned because of social agreement. This atmosphere makes social unearned revenues. Therefore, nyogug cultural tradition becomes an analytical tool. Data were collected through participant observation. The result of this research shows cultural tradition is social unearned revenues recording unity of revenue and expenses. So, measuring it at time of acquisition is also for expenses when it’s incurred. A situation that provides the development of recording transactions based on fairness and equity based on togetherness, as a business entity recognizes revenue and expenses as one. For both of these requirements is the future sacrifice of economic resources. Conditions to bind continue or to become obligatory until satisfied as unearned revenues to economic and physical benefits, revenue and expenses must also be measured and recognized when the nyogug activity occurs. Thus, the measurement of these two accounts at the time of acquisition is also for expenses when incurred.